Measuring risk‐taking in mice: balancing the risk between seeking reward and danger. (28th November 2013) - Dent, Claire L.; Isles, Anthony R.; Humby, Trevor
Abstract Assessing risk is an essential part of human behaviour and may be disrupted in a number of psychiatric conditions. Currently, in many animal experimental designs the basis of the potential 'risk' is loss or attenuation of reward, which fail to capture 'real‐life' risky situations where there is a trade‐off between a separate cost and reward. The development of rodent tasks where two separate and conflicting factors are traded against each other has begun to address this discrepancy. Here, we discuss the merits of these risk‐taking tasks and describe the development of a novel test for mice – the 'predator‐odour risk‐taking' task. This paradigm encapsulates a naturalistic approach to measuring risk‐taking behaviour where mice have to balance the benefit of gaining a food reward with the cost of exposure to a predator odour using a range of different odours (rat, cat and fox). We show that the 'predator‐odour risk‐taking' task was sensitive to the trade‐off between cost and benefit by demonstrating reduced motivation to collect food reward in the presence of these different predator odours in two strains of mice and, also, if the value of the food reward was reduced. The 'predator‐odour risk‐taking' task therefore provides a strong platform for the investigation of the genetic substrates of risk‐taking behaviour using mouse models, and adds a further dimension to other recently developed rodent tests.